EXTRAÇÃO DIRETA DE CELULOSE A PARTIR DE BIOMASSA PARA OBTENÇÃO IN SITU DE COMPÓSITOS ECO-FRIENDLY DE SEMICONDUTORES/CELULOSE. - STINGHEN, Julia Fruhauf; DIAS, Fabricia E. M.; OLIVEIRA, Tarsila M.; ANJOS, Ademir dos; RODRIGUES, Daniela Cristina Manfroi (ANAIS DO ENIC, 2025)
-